2011
DOI: 10.1590/s0103-90162011000300014
|View full text |Cite
|
Sign up to set email alerts
|

15N-labeled nitrogen from green manure and ammonium sulfate utilization by the sugarcane ratoon

Abstract: Legumes as green manure are alternative sources of nitrogen (N) for crops and can supplement or even replace mineral nitrogen fertilization due to their potential for biological nitrogen fixation (BNF). The utilization of nitrogen by sugarcane (Saccharum spp.) fertilized with sunn hemp (Crotalaria juncea L.) and ammonium sulfate (AS) was evaluated using the 15N recovery was evaluated in the two first harvests. In the sum of the three harvests, the highest stalk yields were obtained with a combination of green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…This complementation with C. juncea was reported for corn (Silva et al, 2006) and sugarcane (Ambrosano et al, 2011) and wit early or late legume species in grapevine (Ovalle et al, 2010).…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…This complementation with C. juncea was reported for corn (Silva et al, 2006) and sugarcane (Ambrosano et al, 2011) and wit early or late legume species in grapevine (Ovalle et al, 2010).…”
Section: Introductionsupporting
confidence: 74%
“…Similarly, Ambrosano et al (2011) obtained 4.1% of N-Cj in sugarcane leaves in the 2 nd harvest after C. juncea application, indicating the persistence of residual N in the soil. Fenilli et al, (2008) found in the litter and in the soil 46.3% of applied N after a year of application of marked ammonium sulfate in a coffee plantation.…”
Section: Evaluation In the Second Year Of Growth (December 2010; Aprimentioning
confidence: 75%
See 1 more Smart Citation
“…The previous value of HSP was 31.13Mg ha -1 and differs substantially from that found in this study (64.7Mg ha -1 ) for not irrigate sugarcane with 0kg ha -1 of N. One possible explanation may be the residual effect of nitrogen fertilization in previous seasons (the entire area was fertilized with a rate of 70kg ha -1 of N during the previous crop). AMBROSANO et al (2011) The difference between T1 and T5 managements regarding HSP can be explained by the greater efficiency of the irrigation system (subsurface dripping) compared to not irrigate sugarcane, even with no rainfall amounts sufficient to cause severe deficits for the period studied (Figure 1). …”
Section: ---------------------------------(%)------------------------mentioning
confidence: 99%
“…Residue incorporation studies of legumes using 15 N label indicate that 10 to 34% of the legume N can be recovered in the subsequent rye or wheat crop, 42% in rice, 24% recovery from Velvet bean by corn crop, around 15% of N recovery from sunn hemp by corn plants in no-till system, 30% by maize [51],and 5% of N recovery from sunn hemp by sugarcane [12], and ranged from 19 to 21% when the recovery was observed from sunn hemp by two sugarcane harvest [17].…”
Section: Introductionmentioning
confidence: 99%